Karunia Resort's Efforts in Environmental Conservation Natural Surroundings - Hansa Sasqia Nabella; Muhammad Najih Farihanto (Jogjakarta Communication Conference (JCC), 2024)
Environmental sustainability is one of the things that needs to be preserved and also its balance. Without a sustainable environment, the earth will be far from healthy and disasters will come by themselves. Karunia Resort is one of the resorts in Sleman, Yogyakarta. As a resort that has a natural and traditional concept, Karunia Resort must participate in the preservation of the surrounding environment. This research aims to find out the efforts of Karunia resort in preserving the surrounding nature. The method that researchers use is a qualitative method with a descriptive approach, namely data collected in the form of words, sentences, or images that have meaning and can produce a deeper understanding. The result of the study the theory used by researchers is the SMCR theory which has 4 elements, namely source (the source of information or communicator who plays a role is Mr. Haris Al-Haq as the director of Karunia Resort), message (the message conveyed is an appeal to always protect the environment), channel (the media used by Karunia resort in the persuasive communication process is printed media in the form of posters as well as social media Instagram, WhatssApp, and also Facebook), and receiver (the person who is the target of this persuasive communication is the employees, the surrounding community and also the resort visitors). Karunia resort also strives for several things including the provision of many trash cans, providing counseling to employees, utilizing media to facilitate persuasive communication, and resort governance.